INTRAOVA IAN STUDIES AND FECUNDITY IN NEMIPTERDS JAPONICDS (BLOCH) - Dan, S S (Indian Journal of Fisheries, 2011)
Fecundity i,n Nemipterus japolliclIs (Bloch) va:n ed from to.5 to 80.8 thousize. Among the four equa,(,jonJ, tested, the linear relationship be,tween ength and sands in fish ranging ,in size from 13.0 rtJo 20.9 em. and incre,ased with increasing fecundi,ty was closer tha.n the -rest. It was also found tha.t t’he fish bred twice a yea’r, once in De,cembe,r-Fehrua,ry and then in June-Ju:Jy. The spawning was short and sha’rp.